2018
DOI: 10.13189/lls.2018.060604
|View full text |Cite
|
Sign up to set email alerts
|

Museum Audio Description: Multimodal and 'Multisensory' Translation: A Case Study from the British Museum

Abstract: This paper first illustrates the major revisions, such as a new view of society, the nation, and education, introduced by the New Museology or Museum Studies in the 1980s and 1990s. These changes certainly favoured the development of museum audio description. As museum audio description can be included in the new forms of interactivity, the change of paradigm of interactivity in new museums is analysed and examples are given. Then, a general overview of audio description and its process creation are briefly il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Research has been questioning the feasibility of absolute objectivity in museum AD. For instance, product-oriented studies have focused on the analysis of existing museum ADs and revealed different levels and types of subjectivity in the current practices (Gallego, 2019), also calling for the use of interpretative language in museum AD (Randaccio, 2020). In line with the new directions pursued by "creative media accessibility" (Romero-Fresco, 2021), the benefits of more creative approaches to museum AD have also been investigated, e.g., by proposing "soundpainting" as a form of artistic transcreation (Neves, 2012), as well as "enriched descriptive guide(s)" (Eardley et al, 2017), which are based on multisensory imagery and may "enhance the 'seeing' ability of all people" (Eardley et al, 2017, p. 195).…”
Section: Museum Ad As Intersemiotic Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has been questioning the feasibility of absolute objectivity in museum AD. For instance, product-oriented studies have focused on the analysis of existing museum ADs and revealed different levels and types of subjectivity in the current practices (Gallego, 2019), also calling for the use of interpretative language in museum AD (Randaccio, 2020). In line with the new directions pursued by "creative media accessibility" (Romero-Fresco, 2021), the benefits of more creative approaches to museum AD have also been investigated, e.g., by proposing "soundpainting" as a form of artistic transcreation (Neves, 2012), as well as "enriched descriptive guide(s)" (Eardley et al, 2017), which are based on multisensory imagery and may "enhance the 'seeing' ability of all people" (Eardley et al, 2017, p. 195).…”
Section: Museum Ad As Intersemiotic Translationmentioning
confidence: 99%
“…The aim is to investigate which elements show a higher degree of subjectivity in ADs and AGs produced for a selection of exhibits. Trailing previous studies focusing on subjectivity in museum ADs (Gallego & Colmenero, 2018;Gallego, 2019;Randaccio, 2020), a text-focused analysis based on the appraisal theory (Martin & White, 2005) was conducted on a corpus of ADs and AGs to highlight discrepancies between communicative practices aimed at two target audiences with differing abilities. The corpus includes AD and AG transcripts in English related to a selection of items from different museums in terms of collections, museological tradition, and location (Australia, Germany, Italy and the US).…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines reveal that, apart from providing factual information, stories or narrative are expected to be delivered to enhance the museum experience for BPS visitors (Hutchinson and Eardley 2020). Many studies and practitioners also stress the importance of interpretive and creative AD, and storytelling, as enhancing social, cognitive and emotional experience and memorability (Caro 2016;Randaccio 2018;Hutchinson and Eardley 2019;. For example, in London's Tate Modern, a detailed AD of a painting by Chris Ofili, 'No Woman, No Cry', is delivered in combination with music and stories.…”
Section: Importance Of Accessibility In Museumsmentioning
confidence: 99%